2008
DOI: 10.3354/ame01194
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of planktonic cyanobacteria and microcystin occurrence in Polish water bodies investigated using a polyphasic approach

Abstract: Microscopic measurements of fresh biomass and 16S rRNA gene sequences from clone libraries and denaturing gradient gel electrophoresis (DGGE) were used to investigate cyanobacterial diversity in Polish water bodies in 2002. In addition, measurements of microcystin (MC) concentrations were made. Thirty water samples were taken from 11 water bodies; of these samples, 18 were obtained from the Sulejow Reservoir during regular monitoring from June to October. Intraand extracellular MC concentrations in Sulejow sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Moreover, because of the specificity of the g91-gene, the present study focused exclusively on tracking the interactions between cyanophages from the family Myoviridae and their specific host, the Microcystis genus. Long-term studies have shown the predominance of the genus Microcystis, including M. aeruginosa species, in the Sulejów Reservoir in subsequent years [39,43,45,46]. Cyanophages belonging to the family Myoviridae accompanied cyanobacteria of the genus Microcystis in all surveyed seasons (2009)(2010)(2011)(2012)(2013).…”
Section: Dynamics Of Occurrencementioning
confidence: 98%
“…Moreover, because of the specificity of the g91-gene, the present study focused exclusively on tracking the interactions between cyanophages from the family Myoviridae and their specific host, the Microcystis genus. Long-term studies have shown the predominance of the genus Microcystis, including M. aeruginosa species, in the Sulejów Reservoir in subsequent years [39,43,45,46]. Cyanophages belonging to the family Myoviridae accompanied cyanobacteria of the genus Microcystis in all surveyed seasons (2009)(2010)(2011)(2012)(2013).…”
Section: Dynamics Of Occurrencementioning
confidence: 98%
“…Primers 16S359F and 16S781R, reported by Nübel et al (1997), have been commonly used for specific amplification of the cyanobacterial 16S rDNA fragment (e.g. Boutte et al, 2006Boutte et al, , 2008. PCR was conducted in a total reaction volume of 20 lL containing 6.9 lL of autoclaved ion-exchanged water, 10 lL of Ampdirect Plus (Shimadzu, Kyoto, Japan), 0.1 lL of Ex Taq (Takara Bio, Ohtsu, Japan), 1.0 lL of each primer, and 1.0 lL of template DNA.…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…Among them are Microcystis and Anabaena which frequently dominate the phytoplankton community (Ramírez˗García et al, 2002;Gaytan˗Herrera et al, 2011). Snowella septentrionalis and Aphanizomenon yezoense were also present in this reservoir but these are often non-toxic (Boutte et al, 2008 . Cyanobacterial blooms are a common phenomenon in several water bodies in Mexico primarily due to the prevailing high nutrient and temperature regimes found in these habitats (De la Lanza and García, 2002;Berry et al, 2011;Kosten et al, 2012).…”
Section: Discussionmentioning
confidence: 99%